2018
DOI: 10.2147/dmso.s153151
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of amino acid mixture combined with physical activity promotion for abdominal fat reduction in overweight adults

Abstract: PurposeThe purpose of this study was to test the efficacy of arginine, alanine, and phenylalanine mixture (A-mix) ingestion at 1,500 mg/day in combination with the promotion of physical activity for abdominal fat reduction in overweight adults.MethodsA placebo-controlled, double-blind, parallel-group, randomized trial for 12 weeks combined with a 4-week follow-up period was conducted at a single center in Minato-ku, Tokyo, Japan, between December 2016 and May 2017. Data were analyzed between June and August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…PRD1-BF-1-RIZ1 homologous domain-containing protein-16, which is essential for the induction of beige adipocytes (33,34), is highly expressed in scWAT (i.e., iWAT), but is expressed at an extremely low level in abdominal WAT (i.e., eWAT) (34). In addition, many studies have demonstrated that induction of beige adipocyte forma-tion in scWAT, not abdominal WAT, is significantly associated with a reduction of body fat accumulation and can be a potential therapeutic intervention against obesity (35-38) These previous findings and the current results suggest that the reduction of body fat accumulation promoted by ARF combined with EX in overweight adults (7,8) and diet-induced obesity in mice ( 9) may be associated with the induction of beige adipocyte formation.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…PRD1-BF-1-RIZ1 homologous domain-containing protein-16, which is essential for the induction of beige adipocytes (33,34), is highly expressed in scWAT (i.e., iWAT), but is expressed at an extremely low level in abdominal WAT (i.e., eWAT) (34). In addition, many studies have demonstrated that induction of beige adipocyte forma-tion in scWAT, not abdominal WAT, is significantly associated with a reduction of body fat accumulation and can be a potential therapeutic intervention against obesity (35-38) These previous findings and the current results suggest that the reduction of body fat accumulation promoted by ARF combined with EX in overweight adults (7,8) and diet-induced obesity in mice ( 9) may be associated with the induction of beige adipocyte formation.…”
Section: Discussionsupporting
confidence: 63%
“…Accordingly, EX combined with dietary factors may be expected to increase energy expenditure and enhance other EX-related biological activity. Recent studies have demonstrated that ARF combined with EX can significantly reduce body fat accumulation in overweight adults (7,8) and diet-induced obesity in mice (9). We hypothesized that a combination of ARF and EX would significantly induce beige adipocyte formation and may contribute to control of body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study found that glucagon levels rapidly increased after phenylalanine ingestion (Nuttall et al., 2006), which stimulates and increases fatty acid beta‐oxidation in the liver (Rui, 2014). Another study also found that phenylalanine supplementation, in conjunction with exercise, decreased subcutaneous fat by increasing fat mobilization and oxidation through increased pancreatic alpha‐cell activity (Ueda et al., 2018). In addition, two branched chain amino acids (i.e., valine and isoleucine) were associated with postpartum weight loss among Hispanic women; however, most women met the EAR values for valine (96.0%) and isoleucine (94.9%).…”
Section: Discussionmentioning
confidence: 97%
“…Besides, NO may act via nitrosation- and nitration-mediated posttranslational redox regulatory mechanisms that affect gene and protein expression, enzyme activity, cell morphology, and tissue structure [ 19 ]. Previous studies have shown that l - arginine has beneficial effects on metabolic homeostasis, acting on thermogenesis in BAT and overall oxidative metabolism, resulting in fat mass reduction while sparing lean body mass in both animal and human studies [ 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. However, whether such beneficial effects of l - arginine involve WAT browning is currently unknown.…”
Section: Introductionmentioning
confidence: 99%